2022
DOI: 10.1038/s41467-022-31707-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic retinal pigment epithelium signatures of age-related macular degeneration

Abstract: There are currently no treatments for geographic atrophy, the advanced form of age-related macular degeneration. Hence, innovative studies are needed to model this condition and prevent or delay its progression. Induced pluripotent stem cells generated from patients with geographic atrophy and healthy individuals were differentiated to retinal pigment epithelium. Integrating transcriptional profiles of 127,659 retinal pigment epithelium cells generated from 43 individuals with geographic atrophy and 36 control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 141 publications
1
23
1
Order By: Relevance
“…This finding is presumably the first report of such a difference in a CNV model; it suggests that Adcy1 is involved in CNV formation. On the other hand, we reviewed other transcriptomic studies on CNV and AMD and found that the results of our study did not identify the presence of common genes related to neovascular diseases, such as PNPLA2 , MFGE8 , and DDIT4 ( 27 ). This may be because of the restricted sample numbers used in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…This finding is presumably the first report of such a difference in a CNV model; it suggests that Adcy1 is involved in CNV formation. On the other hand, we reviewed other transcriptomic studies on CNV and AMD and found that the results of our study did not identify the presence of common genes related to neovascular diseases, such as PNPLA2 , MFGE8 , and DDIT4 ( 27 ). This may be because of the restricted sample numbers used in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, another transcriptome and proteome-based study has identified pathways specifically modulated in GA. Induced pluripotent stem cells (iPSCs) were generated from fibroblasts from a cohort of 43 individuals with GA and 36 controls with genotype data [ 57 ]. In this work from Senabouth et al, mitochondrial dysfunction, and specifically, an increase in Complex I linked to a higher oxygen consumption rate, was identified as a central genetic factor associated with GA.…”
Section: Resultsmentioning
confidence: 99%
“…Other data using different experimental approaches also strongly implicate mitochondrial dysfunction as a pathologic feature of AMD. Supportive data from human donor tissue include ultrastructural defects in RPE mitochondria [ 38 ], altered protein content in RPE mitochondria and choroid/Bruch's membrane [ 39 ], increased mtDNA damage in macular RPE from AMD donors [ 9 , 40 ], and decline in mt ETC proteins and function observed in a recent large-scale proteomic study on differentiated RPE cells from AMD patients [ 41 ]. For example, depletion of mtDNA in the RPE cell line, ARPE-19, using ethidium bromide, resulted in induction of genes indicating a switch in metabolism from oxidative phosphorylation to glycolysis and fatty acid metabolism as a mechanism for maintaining energy production [ 42 ].…”
Section: Discussionmentioning
confidence: 99%